IMPLEMENTASI 8 DIMENSI LULUSAN MELALUI PEMBELAJARAN BULUTANGKIS DI SMK BHINNEKA KARAWANG - Singgih Kurnia; Yuniarti Sani Damayanti; Oktaviarini Yahya Rahmadhanty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the level of achievement of 8 dimensions of graduate profiles through badminton learning in vocational high schools. The research method is descriptive quantitative with a survey method. The sample size is 31 students of class X TO 2 SMK Bhinneka Karawang. Data were collected through questionnaires, observations, and documentation. Data were analyzed using descriptive statistics through SPSS 27. The results indicated that the achievement of 8 dimensions of graduate profiles is in the very high category with an average score of 129.39. The collaborative dimension is the aspect with the highest achievement (mean 18.58), followed by communication (18.55), creativity (18.42), and critical reasoning (17.84). Meanwhile, health is the aspect with the lowest achievement (mean 13.87), followed by independence (13.97), citizenship (14.13), and faith and piety (14.03). These findings indicate that badminton learning not only improves physical skills but also contributes to strengthening the character and profile of graduates holistically. Teachers need to optimize activity-based learning so that all dimensions of graduates develop in a balanced manner.